Enrollment Responses to Labour Market Conditions: A Study of the Canadian Market for Scientists and Engineers - Sumon Majumdar; Katsumi Shimotsu (Queen's University, Department of Economics, 2006)
As Canada increasingly structures itself towards a "knowledge based economy", the supply of high-skilled professionals such as engineers and other science graduates acquires more importance. Following the theoretical framework developed by Ryoo and Rosen(2004), we develop and estimate a dynamic supply and demand model for engineers and scientists in Canada. We find that the estimated stock-flow dynamics are supportive of the theoretical model. The relative employment of engineers is quite sensitive to research and development (R&D) expenditures as a fraction of GDP, particularly after 1997. We then use the estimates to develop a dynamic impulse response function. Looking at the impact of a permanent increase in allocation towards R&D, we find that the adjustment process is relatively smooth and the market adjusts in about 2 to 8 years (plus the four years of natural lag in production) to within 80% of the final steady state. For a one-time improvement in R&D allocation, we find that under rational expectations, there is an initial increase in the number of science graduates, but then it falls to below the steady state value and remains there for a long period as the initial increase works its way through the market.
Keywords: J23; J24; J31; J44; I2; 330; dynamic supply and demand; engineers and scientists; R & D expenditure; adjustment dynamics; Wissensgesellschaft; Humankapital; Wissenschaftler; Erwerbstätigkeit; Lohn; Forschungsfinanzierung; Kanada